2019
DOI: 10.1002/chem.201805813
|View full text |Cite
|
Sign up to set email alerts
|

Monodisperse Six‐Armed Starbursts based on Truxene‐Cored Multibranched Oligofluorenes: Design, Synthesis, and Stabilized Lasing Characteristics

Abstract: A series of monodisperse six‐armed conjugated starbursts (Tr1F, Tr2F, and Tr3F) containing a truxene core and multibranched oligofluorene bridges capped with diphenylamine (DPA) units has been designed, synthesized, and investigated as robust gain media for organic semiconductor lasers (OSLs). The influence of electron‐rich DPA end groups on their optoelectronic characteristics has been discussed at length. DPA cappers effectively raise HOMO levels of the starbursts, thus enhancing the hole injection and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…OSLs, including laser operation under short excitation pulses, ranging from 100 femtoseconds (fs) to tens of nanoseconds (ns). [12][13][14][15][16][17][18][19] However, the operation of OSLs under long-pulse excitation of quasi-continuous wave (qCW) or CW regimes remains extremely challenging to achieve, even though it is widely believed as the key stepping stone toward electrically pumped lasers. [13,15,20] The main obstacle of long-pulse OSLs [i.e., millisecond (ms) range] is the indirect generation of triplet excitons (T 1 ) via intersystem crossing (ISC) of radiative singlet excitons.…”
Section: High Mechanical Flexibility and Wavelength Tunability Of Orgmentioning
confidence: 99%
“…OSLs, including laser operation under short excitation pulses, ranging from 100 femtoseconds (fs) to tens of nanoseconds (ns). [12][13][14][15][16][17][18][19] However, the operation of OSLs under long-pulse excitation of quasi-continuous wave (qCW) or CW regimes remains extremely challenging to achieve, even though it is widely believed as the key stepping stone toward electrically pumped lasers. [13,15,20] The main obstacle of long-pulse OSLs [i.e., millisecond (ms) range] is the indirect generation of triplet excitons (T 1 ) via intersystem crossing (ISC) of radiative singlet excitons.…”
Section: High Mechanical Flexibility and Wavelength Tunability Of Orgmentioning
confidence: 99%
“…Lai and his teammates have synthesized six‐armed mono‐dispersed π‐conjugated truxene based multibranched oligofluorene ( 80 a‐c ) capped with diphenylamine (DPA) (Figure ). From the results, it was observed that the compounds capped with DPA starburst oligofluorene can boost its electrical activities by raising the HOMO levels, improving optical, and electroluminescence properties …”
Section: Role Of Truxene System In Photocatalytic Processesmentioning
confidence: 99%
“…[16,17] For example, several conjugated starburst molecules comprising truxene cores and oligofluorene bridges have been recently developed and demonstrated to be of improved hole injectionand transport ability andsuperior optical gain property with al ow threshold of 27.4 nJ pulse À1 ,b ecause of the incorporationo fd iphenylamine cappers. [18] This is an attractive strategy to enhance the hole and electron injection and trans-port at the same time with simultaneous incorporation of electron-donating and electron-withdrawing units into the molecular structures. However,s imultaneously integratinge lectrondonating and electron-withdrawing moieties into one molecule generally results in intramolecular charget ransfer (ICT) characteristics with broadened absorption,n arrowed band gaps, and nonlinear optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…With this aim, it is an effective approach to incorporate electron‐donating units and/or electron‐withdrawing groups into the conjugated molecules to finely adjust the highest occupied molecular orbital (HOMO) and/or the lowest unoccupied molecular orbital (LUMO) levels, thus improving the carrier injection and transport properties . For example, several conjugated starburst molecules comprising truxene cores and oligofluorene bridges have been recently developed and demonstrated to be of improved hole injection and transport ability and superior optical gain property with a low threshold of 27.4 nJ pulse −1 , because of the incorporation of diphenylamine cappers . This is an attractive strategy to enhance the hole and electron injection and transport at the same time with simultaneous incorporation of electron‐donating and electron‐withdrawing units into the molecular structures.…”
Section: Introductionmentioning
confidence: 99%